Clinical course, outcomes and complications of thai pediatric pure type versus mixed type lupus membranous nephritis - Aroonnet M. (2017)
© 2017, Medical Association of Thailand. All rights reserved. Background: Due to the relative infrequency of lupus membranous nephritis (LMN) compared to other types of lupus nephritis (LN) in pediatric patients, the current literature on pediatric LMN is limited. The knowledge regarding clinical manifestations, outcomes and infectious complications are mainly based on studies in the adult population. Similar to disease expression in SLE, the renal manifestations of LMN are affected by environmental factors and vary among racial and ethnic groups. Objective: To describing clinical features, common infectious complications, and outcomes of pediatric-onset LMN in Thailand and the correlation between pure and mixed types of LMN classified by renal pathology. Material and Method: This was a retrospective analysis of 40 patients with LMN as seen in the Pediatric Nephrology Clinic, Maharaj Nakorn Chiang Mai from January, 2003 to December, 2012. Patients were categorized into pure and mixed types of LMN the comparisons of the clinical course, results of treatment and infectious complications between the two types had been analyzed and recorded data for 2 years. Results: Kidney biopsy was performed. Of the 40 patients with LMN, 50% were diagnosed as mixed-type LMN. The clinical symptoms presented including rash, hypertension, edema, serositis and arthritis were found at 57.7%, 45%, 40%, 25% and 25% respectively. All of the patients were treated with an immunosuppressive drug such as: Cyclophosphamide, Azathioprine, Cyclosporine or Mycophenolate mofetil, together with systemic steroids. During the two years follow up, every patient had normal GFR. Twenty nine patients (72.5%) had renal remission in proteinuria with complete remission in 7 patients (17.5%) and partial remission in 22 patients (55%). An average time from the onset to remission was 12 months. GFR and proteinuria were not significant difference between the two groups after treatment. The infections found in patients who received cyclophosphamide include herpes infection, salmonellosis, lung abscess, nocardiosis, giardia intestinalis and cerebral cysticercosis. Furthermore, steroid side effect was avascular necrosis of the hip joint. Conclusion: The mixed-type LMN patients had a higher blood pressure, higher BUN and positive LE cell than those of the pure-type LMN patients. Hypertension at initial presentation can be a predictor of proliferative lesion in renal pathology. However, a proliferative lesion accompanied with LMN does not affect renal outcomes. With similar renal outcomes, the immunosuppressive with low adverse effects may be considered as a preferable treatment.